Short-Term Outcomes of Deep Brain Stimulation of the Subthalamic Nucleus in Patients with Parkinson’s Disease - Pilot Study - Dogru Huzmeli, Esra; Yilmaz, Atilla; Yucekaya, Bircan; Oskay, Deran; Okuyucu, Esra (Journal of Neurological Research And Therapy, 2018)
Background: Deep brain stimulation (DBS) of the subthalamic nucleus (STN) provides efficient treatment for the alleviation of motor signs in patients with Parkinson's disease (PD), but more studies about gait and functionality are needed. We aimed to understand whether short-term DBS treatment will can relieve the symptoms of PD patients, specifically we examined its effect on motor-cognitive-complication parameters, fine motor skills and daily living activity (DLA) of these patients. Method: Ten patients from Mustafa Kemal University Neurosurgery Department were recruited. The assessments were made twice, first time preoperatively, which was within one week prior to the surgery, second time postoperatively, which was 55-65 days post treatment. The motor scores, DLA scores, mental scores and complication scores were measured with Unified Parkinson's Disease Rating Scale (UPDRS), fine motor skills measured with The nine-hole peg test (9-HPT), balance measured with Berg Balance Scale (BBS) and falling risk measured with Timed Up and Go Test (TUG). Results: 10 patients (5 female, 5 male) aged between 40-60 (mean=49.44±6.69 years) were included in the study. Duration of the disease’s mean was 5.60 years. We found significant difference between pre-op and post-op results in UPDRS DLA, UPDRS motor, UPDRS complication, UPDRS total score and TUG tests (Table 2). There was no significant difference between preop-postop assessment in UPDRS mental, BBS and 9-HPT results (p>0.05). Discussion: Balance, walk and fine motor impairment occurs almost always in Parkinson’s disease and resulting in difﬁculties with daily living activities. We found that DBS has positive effect on PD complications, balance and walking abilities. PD patients that have falling risk and multiple motor symptoms may have benefit from DBS.
Keywords: Deep Brain Stimulation; Subthalamic Nucleus; Parkinson Disease; Gait; Balance; Fine Motor Skills